Self-Management and Nutritional Status in Hemodialysis Patients - Istiroha, Istiroha; Azizah, Nur; Ayatulloh, Daviq (Universitas Muhammadiyah Lamongan, 2025)
Introduction: Malnutrition in hemodialysis patients can be caused by various factors, one of which is low self-management ability. This study aims to analyze the relationship between self-management and nutritional status in hemodialysis patients. Methods: The research design used was descriptive analytic with a cross-sectional approach. The sample consisted of 127 chronic kidney disease (CKD) patients undergoing hemodialysis at the Hemodialysis Unit of Petrokimia Gresik Hospital from April to May 2025, using a purposive sampling technique. Data analysis was performed using the Chi-square test with the assistance of SPSS software. Results: The analysis results showed a significant p value=0.037 (<0.05), indicating that there was a significant relationship between self-management and nutritional status in hemodialysis patients. Conclusion: Self-Management is associated with the nutritional status of patients undergoing hemodialysis. Hemodialysis nurses are advised to provide support and education to hemodialysis patients so that patients can practice self-management to maintain their nutritional status. Keywords: Chronic kidney disease, Hemodialysis patient, Nutritional status, Self-management